Predictors of Ventilator Associated Pneumonia of Neonate in a Neonatal and Paediatric Intensive Care Unit (Bangladesh Journal of Child Health, 2019)
Background: Ventilator Associated Pneumonia (VAP) is defined as nosocomial pneumonia develops 48 hours or more after initiation of mechanical ventilation. Hospital acquired infection (HAI) is the second most common infection for the pediatric population. VAP about 20% of all HAI among patients in NICU & PICU. Higher mortality and morbidity rate for mechanically ventilated pediatric patients with VAP compared to those without VAP. Few data & very few researches exist regarding VAP in pediatric patients to identify risk factors of VAP and that might be helpful for preventing VAP. This study was done to find out the predictors of VAP of neonate in Neonatal and Pediatric Intensive Care Unit.Methodology: A prospective cohort study was carried out in NICU & PICU of Dhaka Shishu (Children) Hospital, Dhaka. Neonates those not had pneumonia; requiring mechanical ventilation at least 48 hours in the NICU or PICU were taken for this study. Then VAP patients were selected by radiographic changes after 48 hours of intubation. Portable chest x-ray was done after 48 hours and as required after initiation of ventilation. Then details history were taken and some relevant investigation were done.Result: Majority (51.4%) of the neonates belonged to age group 0-10 days. Male female ratio was 2.8:1. More than half (51.4%) were of gestational age 34 to < 37 weeks. Sixty nine point four percent of the neonates had Weight < 2.5 kg. Transferred from other NICU or PICU was found in 34.7% , prolonged mechanical ventilation was found in 40.3%, reintubation were 36.1%, prior antibiotics use were 73.6%, nosocomial infection were 76.4%, oropharyngeal aspiration were 11.1% and those having VAP were 79.2%. Age group 11-20 days (RR=1.41; 95% CI 1.18 to 1.67), gestational age